Pengaruh Pencarian Sensasi dan Harga Diri terhadap Sexting Behavior pada Remaja Pelaku Sexting di Jakarta - Fristmia Manalu; M. Ramadhana; Silverius Y. Soeharso (Jurnal Ilmiah Psikologi MIND SET, 2018)
Sexting behavior is an activity that is commonly practiced nowadays by teenagers. In this study, sexting behavior is defined as the activity of receiving, sending, receiving and sending sexual content like photos, text messages, or video via mobile phone. This study aims to determine the effect of sensation seeking and self-esteem on sexting behavior in adolescent in Jakarta. The study involved 370 male and female respondents with any backgrounds. The analysis technique used in this research is multiple regression, independent sample t-test and also ANOVA. Some of the results of this study indicates that: (1) there is influences of sensation seeking and self-esteem against sexting behavior, (2) there is influence of sensation seeking against sexting behavior, (3) there is no influence of self-esteem against sexting behavior, and (4) there is difference of sexting behavior in terms of age, education, and sexual orientation. From the results of the study also known that sexting behavior occurs in teenagers, regardless of sexual orientation, educational background, and status of respondents. While it is also known that the most widely referred figure as the purpose of sexting behavior is peers. The most frequent motivation for doing sexting behavior is an attempt to share and try to tease a friend or spouse.